Mutation in cytochrome b gene of mitochondrial DNA in a family with fibromyalgia is associated with NLRP3-inflammasome activation. Issue 2 (13th November 2015) - Cordero, Mario D; Alcocer-Gómez, Elísabet; Marín-Aguilar, Fabiola; Rybkina, Tatyana; Cotán, David; Pérez-Pulido, Antonio; Alvarez-Suarez, José Miguel; Battino, Maurizio; Sánchez-Alcazar, José Antonio; Carrión, Angel M; Culic, Ognjen; Navarro-Pando, José M; et al.
Abstract : Background: Fibromyalgia (FM) is a worldwide diffuse musculoskeletal chronic pain condition that affects up to 5% of the general population. Many symptoms associated with mitochondrial diseases are reported in patients with FM such as exercise intolerance, fatigue, myopathy and mitochondrial dysfunction. In this study, we report a mutation in cytochrome b gene of mitochondrial DNA (mtDNA) in a family with FM with inflammasome complex activation. Methods: mtDNA from blood cells of five patients with FM were sequenced. We clinically and genetically characterised a patient with FM and family with a new mutation in mtCYB. Mitochondrial mutation phenotypes were determined in skin fibroblasts and transmitochondrial cybrids. Results: After mtDNA sequence in patients with FM, we found a mitochondrial homoplasmic mutation m.15804T>C in the mtCYB gene in a patient and family, which was maternally transmitted. Mutation was observed in several tissues and skin fibroblasts showed a very significant mitochondrial dysfunction and oxidative stress. Increased NLRP3-inflammasome complex activation was observed in blood cells from patient and family. Conclusions: We propose further studies on mtDNA sequence analysis in patients with FM with evidences for maternal inheritance. The presence of similar symptoms in mitochondrial myopathies could unmask mitochondrial diseases among patients with FM. On the other hand, the inflammasome complex activation by mitochondrial dysfunction could be implicated in the pathophysiology of mitochondrial diseases.